2022
DOI: 10.1016/j.ssci.2021.105527
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic: Workplace safety management practices, job insecurity, and employees’ organizational citizenship behavior

Abstract: How do organizations and employees react to the COVID-19 pandemic? Can workplace safety management practices (WSPs) maintain employees’ organizational citizenship behavior (OCB) in this time of global health crisis? Can employees’ perceptions of the risk associated with COVID-19 and job insecurity mediate the WSPs–OCB relationship? Drawing upon social exchange and protection motivation theories, this research aims to answer such questions. Analyzing the survey data from 501 Vietnamese employees using SmartPLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 85 publications
3
45
1
2
Order By: Relevance
“…In this vein, specific training should be provided aimed at consolidating and keeping up-to-date knowledge about COVID-19 and its implications on psycho-physical health, as well as stress management practices that on the other side can help support the supervisor to navigate these difficult tasks. Moreover, managers should promote employees’ participation in safety by providing them with opportunities to discuss with each other and consulting with them, to ensure employees’ cooperation in COVID-19 diffusion [ 2 ]. Finally, the present findings also have implications for organizations and the maintenance of their commitment to safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, specific training should be provided aimed at consolidating and keeping up-to-date knowledge about COVID-19 and its implications on psycho-physical health, as well as stress management practices that on the other side can help support the supervisor to navigate these difficult tasks. Moreover, managers should promote employees’ participation in safety by providing them with opportunities to discuss with each other and consulting with them, to ensure employees’ cooperation in COVID-19 diffusion [ 2 ]. Finally, the present findings also have implications for organizations and the maintenance of their commitment to safety.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations typically implement an occupational health and safety management system to control risks and ensure a safe working environment and optimal health for their workers. During the COVID-19 pandemic, however, employees are facing new psychosocial risks in the workplace and every organization has had to place more emphasis on workplace safety management practices to mitigate risks and safeguard health and wellbeing [ 1 , 2 ]. In the field of work and organizational psychology, several studies have been conducted to understand the pandemic’s impact on workers’ wellbeing and mental health and to underline the transformations of the organizational world [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…During COVID‐19, according to the International Labor Organization (2020), to ensure employee health and safety in the workplace, every organization should focus on four WSP components: the management's commitment to safety, safety training, safety regulations and procedures, and employee involvement. Previous studies have demonstrated that these practices have an impact on employee psychology, attitude, and behavior during COVID‐19 (Chi et al, 2020; Lee, 2021; Vu et al, 2022; Yuan et al, 2021). As a result, we used these four aspects to assess PWSPs during COVID‐19 for this research.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…According to the JD–R model, workplace safety practices (WSPs) are job resources that can help reduce employees' burnout and enhance their JP (Bakker et al, 2004; Dlouhy & Casper, 2021). During COVID‐19, WSPs can aid in the reduction of mental health issues among employees by diminishing the perceived fear of an external risk and increasing feelings of psychological safety, resulting in reduced avoidance coping behavior and improved JP (Lee, 2021; Sasaki et al, 2020; Vu et al, 2022; Yuan et al, 2021). However, we have very little understanding of the effect of perceived workplace safety practices (PWSPs) on employee burnout and JP during COVID‐19 from an HRM perspective and the JD–R model lens (Sasaki et al, 2020; Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many construction projects have been halted or postponed due to an interrupted supply chain and employee shortages due to quarantines [ 41 ]. Such changes could threaten workers and evoke a sense of job insecurity, which represents the perception of a potential threat to continuity in their current jobs [ 42 ]. Furthermore, most construction workers, especially in developing countries, come from poor socio-economic backgrounds [ 43 ].…”
Section: Literature Reviewmentioning
confidence: 99%